Antiferromagnetic ordering in the ternary uranium germanide UNi1–xGe2: Neutron diffraction and physical properties studies. (April 2021) - Pasturel, Mathieu; Szlawska, Maria; Ćwik, Jacek; Kaczorowski, Dariusz; Pikul, Adam P.
Abstract: The compound UNi0.45 Ge2 was studied by means of X-ray diffraction (XRD), magnetization, neutron diffraction, specific heat and electrical resistivity measurements performed in wide ranges of temperature and magnetic field. The single-crystal XRD experiment indicated that the material crystallizes in the orthorhombic CeNiSi2 -type structure with the lattice parameters a  = 4.1062(2) Å, b  = 15.9272(8) Å and c  = 4.0461(2) Å. The physical properties measurements showed that it orders antiferromagnetically at T N  = 47 K. The magnetic ordering was confirmed by the neutron diffraction experiment, which revealed that the ordered magnetic moments are aligned along the crystallographic b -axis in a sequence −++−. In strong magnetic fields, a distinct field-induced first-order metamagnetic phase transition occurs, characterized by a large magnetic hysteresis. Temperature and field variations of the electrical resistivity are strongly affected by the atom disorder in the crystallographic unit cell of the investigated compound. Graphical abstract: Image 1 Highlights: UNi0.45 Ge2 crystallizes in a Ni-deficient CeNiSi2 orthorhombic structure-type. Antiferromagnetic ordering below TN  = 47 K with moments oriented along the b -axis. Electrical (magneto)resistivity is influenced by crystallographic disorder. Metamagnetic transition above 10 T with huge hysteresis (4 T at 2 K): 1 st order?